Characteristics of period-one oscillations in semiconductor lasers subject to optical injection - Sheng-Kwang Hwang; Jia-Ming Liu; White, J.K. (IEEE journal of selected topics in quantum electronics, 2004)
The characteristics of period-one oscillations in semiconductor lasers subject to optical injection are experimentally and theoretically investigated. Attention is mainly paid to the relative dependence of the frequency and the magnitude between the principal oscillation and the first sideband in period-one oscillations as a function of the detuning frequency and the injection strength of the injection signal. The frequency separation between the two signals is found to decrease as the injection strength and the detuning frequency reduce. The magnitude of the principal oscillation decreases with the decreasing injection strength and the increasing detuning frequency, while that of the first sideband grows at the same time. At some operating conditions, the magnitude of the first sideband dominates that of the original principal oscillation, resulting in a frequency shift of the principal oscillation from the injection frequency to the first sideband. Similar studies are also done for the stable injection locking to explore the transition of the frequency and the magnitude characteristics across the Hopf bifurcation line. The effects of different bias current levels of the injected laser on the frequency and the magnitude characteristics of period-one oscillations are also investigated.